DEVELOPMENT OF TECHNOLOGY FOR PRODUCING LEATHER FROM AFRICAN CATFISH SKINS - Ismatullayev, Nizom; Shamsiyeva, Mahbuba (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The article develops and substantiates a technological system for processing African catfish skin and producing leather from it. It is emphasized that taking into account the individual characteristics of fish skin during processing creates the prerequisites for obtaining high-quality products. It is established that processing fish skin has socio-economic advantages: it is a renewable resource, facilitates waste utilization, and enables the production of a new range of leather materials. There are two most important new features in this article: one of this is a personalised degreasing protocol for the high lipid content (22.8±2.1%) and second one is better chrome tanning settings that make collagen more stable. The key point of the process is to work at low temperatures and keep the pH level just right so that enzymes do not break down the skin. Although, the leather taken from this process has a grain pattern and mechanical properties that make it good for high-end uses.